Catecholamines synthesizing enzymes in vascular cells and their hypoxic regulation - Rafiq, Amir; Justus Liebig University Giessen (My University, 2012)
Catecholamines (dopamine, norepinephrine and epinephrine) are physiologically important as they are involved in a number of body functions and also act as neurotransmitters. Dopamine is a metabolic intermediate in the formation of norepinephrine and epinephrine and a well known neurotransmitter in the central nervous system. In most of the mammalian systemic arteries, dopamine acts as a potent vasodilator. The vascular effects of dopamine are mediated via specific G protein-coupled receptors (D1-D5). The present study aimed to look for the presence of enzymatic machinery (tyrosine hydroxylase = TH; DOPA-decarboxylase = DDC; dopamine-beta-hydroxylase = DbetaH; phenylethanolamine-N-methyltransferase = PNMT) required to synthesize catecholamines in rat arteries, and their regulation in response to hypoxia (1% O2) in endothelial (EC) and vascular smooth muscle cells (VSMC). Quantitative RT-PCR served to estimate mRNA content, and western blotting was used to test for TH protein expression. Furthermore, we also looked for the expression of the rate-limiting enzyme of catecholamine synthesis, TH, by quantitative RT-PCR, immunohistochemistry and western blotting in the intact vessels (rat thoracic aorta, abdominal aorta, superior mesenteric artery [SMA] and femoral artery). Expression of mRNA of all four enzymes of the catecholamine synthesis pathway was detected and quantified in rat thoracic and abdominal aorta, SMA and femoral artery. It was observed that these arteries express different levels of mRNA content of these enzymes with PNMT being least abundant. TH protein was also detected in these arteries by immunolabelling and western blot analysis. TH expression in these arteries suggests active synthesis of dopamine and/or other catecholamines in these vessels. Previously, TH mRNA expression has been reported in rat aorta and it has been suggested that this might be the result of paraganglia contamination during sampling process. No paraganglia were detectable in immunohistochemical preparation of rat aorta suggesting that this part of vascular tree is itself capable of synthesizing catecholamines. Rat pulmonary and aortic EC were isolated and cultured. These cells were characterized by DiI-Ac-LDL uptake and by immunolabeling with anti-vWF antibody. VSMC were isolated and cultured from thoracic and abdominal aorta and characterized by immunolabeling with anti alpha-smooth muscle actin antibody. Under normoxic conditions, EC and VSMC express mRNAs coding for all of the enzymes involved in catecholamine synthesis. These vascular cells were exposed to hypoxia (1% O2) for 6, 12 and 24 hours. Using real-time RT-PCR we detected the mRNAs for the complete or partial enzymatic machinery necessary for catecholamine synthesis in these cells. In rat pulmonary EC, hypoxia caused an up-regulation of TH mRNA by 25-fold after 24 h, of DbetaH mRNA by 8-fold after 6 and 24 h, whereas DDC and PNMT mRNA content were not significantly different after hypoxic exposure. In contrast, no significant effect of hypoxia on the regulation of the enzymatic machinery was observed in rat aortic EC. In VSMC, TH mRNA was qualitatively detectable while DDC mRNA content was too low to be detected. No statistically significant regulation of DbetaH and PNMT mRNA content was observed after hypoxic exposure in VSMC. This suggests that vascular cells are capable of catecholamine synthesis and this synthesis is differentially regulated under hypoxic conditions. This is the first study providing evidence of expression of catecholamine synthesis enzymes in isolated vascular cells. Previously, Kuncova et al., 2007, had shown that the presence of catecholamines in rat aorta and SMA. Chemical sympathectomy with the neurotoxin, 6-hydroxydopamine, significantly reduced norepinephrine and epinephrine levels, while dopamine content was unaffected. Functional studies using rat SMA showed an endothelium-dependent vasodilation in response to fall of PO2 approximately -25 mm Hg, which could be blocked by the specific dopamine D1 receptor antagonist SCH23990, suggesting possible role of locally produced dopamine in the vasodilation. This study suggests that there are two sources of catecholamines, in particular dopamine - neuronal and non-neuronal - and the non-neuronal synthesis is carried out by both principal cell types of vascular wall, i.e. EC and VSMC. Catecholamines produced by vascular cells are released in the event of hypoxia. This locally synthesized and released dopamine mediates vasodilation and might help in an increased O2 and nutrient supply to the affected organ.

Katecholamine (Dopamine, Noradrenalin und Adrenalin) spielen eine physiologisch wichtige Rolle als Neurotransmitter sowie in der Regulation verschiedenster Körperfunktionen. Dopamin ist ein Zwischenprodukt in der Synthese von Noradrenalin und Adrenalin sowie auch selbst ein Neurotransmitter im zentralen Nervensystem. In den systemischen Arterien des Säugers ist Dopamin zumeist ein potenter Vasodilatator. Die vaskulären Effekte von Dopamin werden über spezifische G Protein-gekoppelte Rezeptoren (D1 - D5) vermittelt. In der vorliegenden Studie wurde das Vorkommen der enzymatischen Maschinerie zur Katecholaminsynthese (Tyrosinhydroxylase = TH, DOPA-Decarboxylase = DDC; Dopamin-beta-Hydroxylase = DbetaH, Phenyläthanolamin-N-Methyltransferase = PNMT) in Arterien der Ratte untersucht sowie auch deren Hypoxie abhängige Regulation in Endothel-(EC) und vaskulären glatten Muskelzellen (VSMC). Der Gehalt an mRNA wurde über quantitative RT-PCR untersucht, TH-Proteinexpression wurde mittels Western Blot bestimmt. Weiterhin wurde die Expression des geschwindigkeitsbestimmenden Enzyms der Katecholaminsynthese (TH) mittels quantitativer RT-PCR, Immunhistochemie und Western Blot in intakten Gefäßen (Brustaorta, abdominale Aorta, obere Mesenterialarterie und Femoralarterie) untersucht.Expression der mRNA für alle vier Enzyme war nachweisbar und wurde in allen untersuchten Arterien quantifiziert. Hierbei zeigten sich für die einzelnen Enzyme unterschiedliche mRNA-Mengen, wobei PNMT die niedrigste Expression aufwies. TH-Protein wurde in diesen Arterien immunhistochemisch und im Western Blot nachgewiesen. Die TH-Expression in diesen Arterien lässt eine aktive Synthese von Dopamin und/oder anderen Katecholaminen erwarten. In einer früheren Arbeit wurde TH-mRNA-Expression in der Aorta der Ratte gezeigt und es wurde angenommen, dass dies durch eine Kontamination durch Paraganglien während der Probengewinnung beruhte. In den immunhistochemischen Untersuchungen in dieser Arbeit waren Paraganglien nicht nachweisbar, was darauf hinweist, dass die Aorta selbst zur Katecholaminsynthese in der Lage ist.EC wurden aus der Aorta und Lungenarterie der Ratte isoliert und kultiviert. Sie wurden durch den Nachweis der DiI-Ac-LDL-Aufnahme und durch Immunmarkierung mit anti-vWF-Antikörpern charakterisiert. VSMC wurden von der Brust und der Abdominalaorta isoliert und kultiviert, ihre Charakterisierung erfolgte durch Immunmarkierung mit anti alpha-smooth muscle actin Antikörper. Unter normoxischen Kulivierungsbedingungen exprimieren EC und VSMC mRNA für alle Enzyme der Katecholaminsynthese. Diese Gefäßzellen wurden dann für 6, 12 und 24 Stunden hypoxischer (1% O2) Atmosphäre exponiert. Real-time RT-PCR zeigte die mRNA für alle oder einen Teil der Enzyme der Katecholaminsynthese in diesen Zellen. In den Lungen-EC der Ratte bewirkte Hypoxie-Exposition eine Hochregulation der TH-mRNA um das 25-fache nach 24 Stunden und der DbetaH mRNA um das 8-fache nach 6 und 24 Stunden, wohingegen DDC- und PNMT-mRNA Gehalt sich nicht signifikant veränderten. Im Gegensatz dazu zeigten sich keine signifikanten Veränderungen in Aorten-EC der Ratte nach hypoxischer Exposition. In VSMC war TH-mRNA qualitativ nachweisbar, wohingegen der DDC-mRNA-Gehalt unter der Nachweisgrenze lag. Hypoxie-Exposition der VSMC resultierte nicht in einer statistisch signifikant nachweisbaren Regulation des DbetaH- und PNMT-mRNA-Gehalts. Diese Ergebnisse zeigen, dass Zellen der Gefäßwand zur Katecholaminsynthese in der Lage sind und dass diese Synthese unter hypoxischen Bedingungen unterschiedlich reguliert wird.Dies ist die erste Studie, die einen direkten Nachweis der Expression der Katecholaminsynthese-Enzyme in isolierten Gefäßwandzellen liefert. Kuncova und Mitarbeiter zeigten zuvor in 2007 das Vorkommen von Katecholaminen in der Aorta und oberen Mesenterialarterie der Ratte. Chemische Sympathektomie mit dem Neurotoxin 6-Hydroxydopamin führte zu einer signifikanten Reduktion des Noradrenalin- und Adrenalingehaltes, während der Dopamingehalt konstant blieb. Funktionelle Studien an der oberen Mesenterialarterie der Ratte zeigten eine endothelabhängige Vasodilatation bei einem Abfall des PO2 um 25 mmHg, welche durch den spezifischen Dopamin D1 Rezeptorantagonisten SCH23990 aufgehoben wurde. Dies weist auf eine wahrscheinliche Rolle des lokal produzierten Dopamin in der Vasodilatation hin.Die Ergebnisse dieser Studie lassen zwei verschiedene Quellen von Katecholaminen, insbesondere Dopamin, in der Gefäßwand annehmen neuronal und nicht-neuronal und die nicht-neuronale Synthese kann von den beiden vorherrschenden Zellen der Gefäßwand (EC und VSMC) bewerkstelligt werden. Von Gefäßmuskelzellen hergestellte Katecholamine können unter hypoxischen Bedingungen freigesetzt werden. Dieses lokal synthetisierte und freigesetzte Dopamin vermittelt Gefäßerweiterung und trägt wahrscheinlich zu einer verbesserten Sauerstoff- und Nährstoffversorgung der abhängigen Organe bei.
Keywords: ddc:610